How to win friends and influence people - Carnegie, Dale, 1888-1955 (Simon & Schuster, 2009)
Carnegie's classic bestseller--an inspirational personal-development guide that shows how to achieve lifelong success--is now in a newly packaged edition, the first hardcover release of this classic since 1981.